Using TOGAF 9.1 To Analyse and Model the Public Library Business Process - Aditya Rachmadi; Widhy Hayuhardhika Nugraha Putra Putra; Andi Reza Perdanakusuma (SISFOTENIKA, 2023)
The government of Kota Batu claimed that their Public Services are organized based on Good Governance practices. The library sector, under the control of the Library and Archives Service, is guided by the principles of good governance in carrying out each of its processes, especially in delivering library services to the public. This research will define the components that form the basis of the activities carried out by the Library Sector, especially in the delivery of mobile library services. Insights from the results of the identification of types of services, stakeholders, issues that occur, values, and motivations serve as a guide in the preparation of the components that form a business processes model such as participants, functions, flows, artefacts, and rules that apply based on the context of services being delivered. Process models are developed using the Business Process Modeling Notation (BPMN) modelling language. The study of the ongoing process is using Failure Mode and Effect Analysis (FMEA) which defined that there are five activities identified with the highest categories of risk. From this research, we conclude two solutions, namely the development document management system with digital signature features and electronic scheduling that is connected to the asset management system.